Introduction to Nigerian legal method (Ile Ife, Nigeria : Kuntel Publishing House, 1999)
Legal method is the only law subject presently being offered by part one law students of Nigerian universities (the students) under the new Nigerian Universities Commission's (NUC) approved syllabus for law. While many law students usually excel in courses taken in cognate faculties with considerable ease, it is regrettable that most of them performing poorly in legal method. it is therefore not usual to find many students in advance classes repeating the course after failed attempts. The "headache" of the students is compounded by the fact that legal method. by nature is not a course that can be easily "crammed" or should even be "crammed". A students who manages to "cram" it for the sake of merely passing examination may unwittingly weaken the foundation of this legal education. Therefore unless start the legal training with a feeling of frustration and discouragement.
includes bibliographial references and index
aau, 27/07/2022
Loans
Keywords: Legal method; Nigeria